1995
DOI: 10.1002/bies.950170507
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotide exchange factors: Activators of the Ras superfamily of proteins

Abstract: Ras proteins function as critical relay switches that regulate diverse signaling pathways between cell surface receptors and the nucleus. Over the past 2-3 years researchers have identified many components of these pathways that mediate Ras activation and effector function. Among these proteins are several guanine nucleotide exchange factors (GEFs), which are responsible for directly interacting with and activating Ras in response to extracellular stimuli. Analogous GEFs regulate Ras-related proteins that serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
159
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(166 citation statements)
references
References 71 publications
5
159
0
2
Order By: Relevance
“…Originally, guanine nucleotide exchange factors (GEFs) were thought to activate Ras exclusively at the PM. [39] Later, it was found that Ras was also switched-on at different endomembranes and by distinct GEFs. For example, Ras is activated by Ras-GRP GEFs at the GC, [40,41] whereas SOS and Ras-GRF GEFs function at the ER.…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…Originally, guanine nucleotide exchange factors (GEFs) were thought to activate Ras exclusively at the PM. [39] Later, it was found that Ras was also switched-on at different endomembranes and by distinct GEFs. For example, Ras is activated by Ras-GRP GEFs at the GC, [40,41] whereas SOS and Ras-GRF GEFs function at the ER.…”
Section: Ras: An Actor On Many Stagesmentioning
confidence: 99%
“…11 A number of RasGEFs have been characterized. 4,12 Sos1, and Sos2, for example, are normally localized in the cytosol, but in response to extracellular stimulation, they are recruited to the plasma membrane. Through preliminary analysis of cellular distribution, we carried out subcellular fractionation studies, in which we could precisely show that RasGEF1b is predominantly localized at HMs (Figure 3c; Supplementary Figure 4).…”
Section: Cloning Expression and Subcellular Localization Of Rasgef1mentioning
confidence: 99%
“…Ras is a point of convergence for diverse extracellular signal-stimulated pathways function as GDP/GTP regulated switches (H-Ras, NRas, K-Ras4A and K-Ras4B) (Barbacid, 1987;Bourne et al, 1990;Boguski and McCormick, 1993;Quilliam et al, 1995). The two forms of K-Ras diverge solely in their COOH-terminal 25 amino acids as a consequence of alternate exon utilization.…”
Section: Introductionmentioning
confidence: 99%